Morphology and phylogeny of the centrohelid heliozoans Raphidocystidae and their ability to consume cyanobacteria - Dmitry G. Zagumyonnyi; Yingchun Gong; Da Huo; Denis V. Tikhonenkov (PLoS ONE, 2025)
The centrohelid family Raphidocystidae is a large group of heliozoans whose morphology and biology are poorly understood and whose taxonomy and phylogenetic relationships are currently confusing. Here, we report the results of a study of clonal cultures of raphidocystids belonging to the species Raphidocystis tubifera, R. ambigua, R. marginata and R. symmetrica. The cells were examined using light microscopy as well as scanning and transmission electron microscopy. New data on the morphology of the studied species were obtained and compared with other representatives of Raphidocystidae. For the first time, R. ambigua and R. symmetrica are reported for Kazakhstan and China, respectively. Cases of taxonomic confusion within Raphidocystidae have been detected and discussed. Molecular phylogenetic analyses based on 18S rRNA sequences clarified the relationships within raphidocystids and confirmed that scales with smooth surfaces are apparently characteristic of the common ancestor of all Raphidocystidae, and scales with a reticular structure were acquired evolutionarily later. Cysts within the Raphidocystidae species were apparently a later evolutionary acquisition. The ability of centrohelid heliozoans to consume cells of toxic and nontoxic cyanobacteria, which cause the most dangerous harmful algal blooms, has been demonstrated for the first time.